The Effect of Digital Transaction Growth, Firm Size, and Liquidity on Banking Profitability on the IDX (2021-2024) - Hayu Febrian Shintadevi; Nur Lailiyatul Inayah (Universitas Bhayangkara Surabaya, 2026)
This study examines the effect of digital transaction growth, firm size, and liquidity on the profitability of banking companies listed on the Indonesia Stock Exchange for the 2021–2024 period. The rapid digitalization of the financial sector and inconsistencies in prior research findings drive this investigation. Using a quantitative approach with multiple linear regression on ten sample banks, the results indicate that only digital transaction growth significantly influences profitability partially. Simultaneously, all variables significantly affect financial performance. Digital transaction growth emerges as the most dominant factor in driving profits. Banks are advised to strengthen their digital service infrastructure to optimize future earnings.